Olfactory and gustatory dysfunctions in COVID-19 patients: From a different perspective - Polat, Burcu; Helvacı Yılmaz, Nesrin; Altın, Gökhan; Atakcan, Zeynep; Mert, Ali (Lippincott Williams & Wilkins, 2021)
Purpose: The prevalence of sensory disorders (smell and/or taste) in affected patients has shown a high variability of 5% to 98% during the COVID-19 outbreak, depending on the methodology, country, and study. Loss of smell and taste occurring in COVID-19 cases are now recognized by the international scientific community as being among the main symptoms of the disease. This study investigates loss of smell and taste in outpatients and hospitalized patients with laboratory-confirmed COVID-19 infection. Methods: Enrolled in the study were patients with a positive PCR test for COVID-19. Excluded were patients with chronic rhinosinusitis, nasal polyposis, common cold, influenza, and olfactory/gustatory dysfunction predating the pandemic. Patients were asked about changes in their sense of smell and taste by structured questionnaire. Their status was classified according to severity of the symptoms. Results: A total of 217 patients were included in the study, of whom 129 received outpatient treatment, whereas 88 were hospitalized; mean age was 41.74 years (range18-76), 59.4% were male. At evaluation for olfactory dysfunction, 53.9% of the patients were found to be normal, whereas 33.2% were anosmic. No gustatory dysfunction was found in 49.8% of patients, whereas in those with loss of taste, the most commonly recorded symptom was ageusia. Anosmia was significantly more common in outpatients (P = 0.038). Presentation of chemosensorial symptoms in women was higher than in men (P = 0.009). No correlation was found between olfactory and gustatory dysfunction and age (P = 0.178). Conclusions: About one-half of our patients presented olfactory and/or gustatory deficits, and loss of smell was more common in mild cases. It should be considered; a sudden, severe, and isolated loss of smell and/or taste may also be present in COVID-19 patients who are otherwise asymptomatic. We suggest that identification of persons with these signs and early isolation could prevent spread of the disease in the community.
Keywords: Ageusia; Anosmia; COVID-19; Gustatory; Hospitalization; Olfactory; SARS-CoV-2